The Influence of Tax Knowledge, Taxpayer Awareness, Tax Sanctions and Fiscus Services on Taxpayer Compliance Registered with KPP Pratama Jakarta Kemayoran in 2022 - Safitri, Awalina Dea (Politeia : Journal of Public Administration and Political Science and International Relations, 2023)
This study discusses the effect of knowledge of Taxation, taxpayer awareness, Tax sanctions and tax authorities services on taxpayer compliance. The purpose of this study was to determine the effect of knowledge of Taxation, taxpayer awareness, Tax sanctions and Tax Authority services on taxpayer compliance. The method used in this study is a quantitative approach. The population in this study is a taxpayer registered in KPP Pratama Jakarta Kemayoran. The total population of taxpayers in 2022 is 144,041. Determination of the number of samples in this study using the slovin formula with the results of 100 respondents. Data analysis methods used are Instrument Test with validity test and reliability test, descriptive statistical test and followed by classical assumption test and hypothesis test with T test, F test, correlation coefficient Test and determination coefficient Test (R2 test). Based on the results of the study, it is known that knowledge of Taxation has a significant effect with a count of 4,084, taxpayer awareness has a significant effect of 3,505, Tax sanctions have a significant effect of 3,285 and tax services have a significant effect of 8,127. Simultaneous test results (test F) showed Fcount of 16,696 with significant (0,000) <0.05 so that the hypothesis that the knowledge of Taxation, taxpayer awareness, Tax sanctions and Services Tax Authorities on taxpayer compliance can be accepted. The effect together is equal to 41.3%.